It is given in this problem that $x^4 + \dfrac{1}{x^4}$ is equal to $\dfrac{-16}{27}$

$x^4 + \dfrac{1}{x^4} = \dfrac{-16}{27}$

The value of $x+\dfrac{1}{x}$ can be found by reducing the power of the given equation. In order to do it, express $x$ raised to the power of $4$ in terms of $x$ squared.

${(x^2)}^2 + \dfrac{1}{{(x^2)}^2} = \dfrac{-16}{27}$

$\implies {(x^2)}^2 + {\Bigg(\dfrac{1}{x^2}\Bigg)}^2 = \dfrac{-16}{27}$

The two terms of the left hand side equation are in square form. So, they can used to convert them as whole square of sum of terms. In order to convert it, add $2$ to left hand side equation and subtract it by same number.

$\implies {(x^2)}^2 + {\Bigg(\dfrac{1}{x^2}\Bigg)}^2 + 2 -2 = \dfrac{-16}{27}$

We know that the product of numbers $2$ and $1$ is equal to $2$. So, the number $2$ can be express as the product of the numbers $2$ and $1$.

$\implies {(x^2)}^2 + {\Bigg(\dfrac{1}{x^2}\Bigg)}^2 + 2 \times 1 -2 = \dfrac{-16}{27}$

In L.H.S, $x^2$ and $\dfrac{1}{x^2}$ are two terms in square form. The product of them is equal to $1$. Therefore, write the number $1$ as the division of $x^2$ by $x^2$ term.

$\implies {(x^2)}^2 + {\Bigg(\dfrac{1}{x^2}\Bigg)}^2 + 2 \times \dfrac{x^2}{x^2} -2 = \dfrac{-16}{27}$

Take $x^2 = a$ and $\dfrac{1}{x^2} = b$.

$\implies a^2 + b^2 + 2ab -2 = \dfrac{-16}{27}$

The first three terms of the left hand side equation is the expansion of the a plus b whole square formula.

$\implies {(a + b)}^2 -2 = \dfrac{-16}{27}$

$\implies {(x^2)}^2 + {\Bigg(\dfrac{1}{x^2}\Bigg)}^2 + 2 \times x^2 \times \dfrac{1}{x^2} -2 = \dfrac{-16}{27}$

Replace the assumed values of $a$ and $b$ terms.

$\implies {\Bigg(x^2 + \dfrac{1}{x^2}\Bigg)}^2 = 2 -\dfrac{16}{27}$

$\implies {\Bigg(x^2 + \dfrac{1}{x^2}\Bigg)}^2 = \dfrac{2}{1} -\dfrac{16}{27}$

$\implies {\Bigg(x^2 + \dfrac{1}{x^2}\Bigg)}^2 = \dfrac{54 -16}{27}$

$\implies {\Bigg(x^2 + \dfrac{1}{x^2}\Bigg)}^2 = \dfrac{38}{27}$

Take square root both sides.

$\implies \sqrt{{\Bigg(x^2 + \dfrac{1}{x^2}\Bigg)}^2} = \sqrt{\dfrac{38}{27}}$

Once again, use the same above procedure to reduce the power of square form terms.

$\implies x^2 + \dfrac{1}{x^2} = \sqrt{\dfrac{38}{27}}$

$\implies x^2 + \dfrac{1}{x^2} + 2 -2 = \sqrt{\dfrac{38}{27}}$

$\implies x^2 + \dfrac{1}{x^2} + 2 \times 1 -2 = \sqrt{\dfrac{38}{27}}$

$\implies x^2 + \dfrac{1}{x^2} + 2 \times \dfrac{x^2}{x^2} -2 = \sqrt{\dfrac{38}{27}}$

$\implies x^2 + \dfrac{1}{x^2} + 2 \times x^2 \times \dfrac{1}{x^2} -2 = \sqrt{\dfrac{38}{27}}$

$\implies x^2 + \dfrac{1}{x^2} + 2 \times x^2 \times \dfrac{1}{x^2} = 2 + \sqrt{\dfrac{38}{27}}$

$\implies {\Bigg(x + \dfrac{1}{x}\Bigg)}^2 = 2 + \sqrt{\dfrac{38}{27}}$

$\implies \sqrt{{\Bigg(x + \dfrac{1}{x}\Bigg)}^2} = \sqrt{2 + \sqrt{\dfrac{38}{27}}}$

$\therefore \,\,\,\,\, x + \dfrac{1}{x} = \sqrt{2 + \sqrt{\dfrac{38}{27}}}$

Therefore, the value of $x + \dfrac{1}{x}$ is equal to $\sqrt{2 + \sqrt{\dfrac{38}{27}}}$

Latest Math Topics

Jun 05, 2023

Jun 01, 2023

May 21, 2023

May 16, 2023

May 10, 2023

Latest Math Problems

Jun 08, 2023

May 09, 2023

A best free mathematics education website that helps students, teachers and researchers.

Learn each topic of the mathematics easily with understandable proofs and visual animation graphics.

A math help place with list of solved problems with answers and worksheets on every concept for your practice.

Copyright © 2012 - 2022 Math Doubts, All Rights Reserved